1969
DOI: 10.3181/00379727-130-33754
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Protection of Chick Embryo against Endotoxin by Isoproterenol, Polymyxin B Sulfate, and Hydrocortisone

Abstract: The lethal effect of endotoxin in the 10-11 day chick embryo could be prevented by the administration of hydrocortisone ( 1 ) , isoproterenol (2), or polymyxin B sulfate (3) when endotoxin and the protectorant were given simultaneously. Since the properties of these agents differ, a variance in protection could be anticipated with a change in the time between the administration of endotoxin and protectorant. To preclude a nonspecific effect of in vitro mixing of endotoxin and a protectorant, separate administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1974
1974
1979
1979

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Those that did not have a definitive gel within 24 hr were judged to have negligible or no endotoxin activity. A standard curve was constructed using The antibiotic polymyxin B sulfate has been shown to neutralize known concentrations of Escherichia coli 0127B8 endotoxin; the endotoxin lethality in chick embryos and adrenalectomized mice times obtained were read off the standard curve and were calcu- (8,13,15) and to prevent endotoxin-induced leukopenia, throm-lated to represent micrograms of endotoxin activity per milliliter bocytopenia, disseminated intravascular coagulation, and renal of plasma. Each new lot of lysate was tested and was considered cortical necrosis in rabbits (3,14) and the fall in cardiac output, active if a solid gel formed between 2.5 and 4.0 min after the mean arterial pressure, and systemic vascular resistance in dogs addition of 1.0 pg E. coli endotoxin (0127:B8, Difco Laboratories, (12).…”
Section: Summarv Polymyxin B Has Antiendotoxin Activity Which Is Distmentioning
confidence: 99%
See 1 more Smart Citation
“…Those that did not have a definitive gel within 24 hr were judged to have negligible or no endotoxin activity. A standard curve was constructed using The antibiotic polymyxin B sulfate has been shown to neutralize known concentrations of Escherichia coli 0127B8 endotoxin; the endotoxin lethality in chick embryos and adrenalectomized mice times obtained were read off the standard curve and were calcu- (8,13,15) and to prevent endotoxin-induced leukopenia, throm-lated to represent micrograms of endotoxin activity per milliliter bocytopenia, disseminated intravascular coagulation, and renal of plasma. Each new lot of lysate was tested and was considered cortical necrosis in rabbits (3,14) and the fall in cardiac output, active if a solid gel formed between 2.5 and 4.0 min after the mean arterial pressure, and systemic vascular resistance in dogs addition of 1.0 pg E. coli endotoxin (0127:B8, Difco Laboratories, (12).…”
Section: Summarv Polymyxin B Has Antiendotoxin Activity Which Is Distmentioning
confidence: 99%
“…Quantitative colony counts using heparinized whole blood were performed by pour plate technique on 5% blood agar plates his investigation and other reports have shown that ~o l~m~x i n (h4icro-~ech Diagnostics, Tucson, AZ). The plates were incubated B sulfate neutralized endotoxin effects in animals given purified at 370 and 24 hr later the small, mucoid gray, nonhemolytic endotoxin, dead endotoxin-containing organisms, and gram-nega-colonies were counted, tive septicemic animals (3,6,8,(12)(13)(14)(15). The antiendotoxin effect ~~~~~i~i~~d plasma was obtained by ofthe blood of the antibiotic appears to be separate from its antimicrobial at 150 at 40 for 10 min, ~h~ plasma was divided equally and effects.…”
Section: Summarv Polymyxin B Has Antiendotoxin Activity Which Is Distmentioning
confidence: 99%
“…Since bacterial endotoxin has been chiefly implicated in producing these complications, numerous attempts have been made to prevent or modify the toxic effect of endotoxin in various animal models. Polymyxin B sulfate administered simultaneously with endotoxin has been shown to reduce endotoxin lethality in chicken embryos (7,15) and adrenalectomized mice (13) and to prevent the generalized Shwartzman reaction in rabbits (5,14). Sodium colistimethate has similar activity but is less effective than polymyxin B (4,15).…”
mentioning
confidence: 99%
“…A 10,000-fold range in the relative susceptibility of different endotoxins to inactivation by polymyxin B was found. The endotoxin most susceptible to polymyxin B was derived from an organism resistant to polymyxin B by disk sensitivity testing, suggesting that the bacteriocidal and endotoxin detoxifying properties of polymyxin need not be directly related.Recent studies have demonstrated the capacity of polymyxin B to protect animals from a variety of toxic effects of endotoxin, including the generalized Schwartzman reaction (5, 23), diffuse intravascular coagulation (6, 7), renal cortical necrosis (6, 7), leukopenia (6, 7), and death (6,12,21,23). The limulus gelation test, developed by Levin and others (13,14), has provided a useful in vitro means to assess an endotoxin activity which corresponds with in vivo indices of toxicity (3,15,24).…”
mentioning
confidence: 99%